APPLICATION OF THE FIFO MODEL IN THE DRUG INVENTORY INFORMATION SYSTEM AT THE ASYFA KRUENG MANE PHARMACY - Sayed Fachrurrazi; Muthamainnah Muthamainnah; Muhammad Fajar Maulana; Angga Pratama (Universitas Mulia, 2023)
Asyfa Krueng Mane Pharmacy is a business entity engaged in the sale of drugs. The drug supply data processing system that was carried out at the Asyfa Krueng Mane Pharmacy still uses ordinary stationery to process drug supply data so that it is deemed less effective and efficient. Therefore, there is a need for an information system that can be used to assist and support the efficiency of the drug data processing process at the Asyfa Krueng Mane Pharmacy using the FEFO (First First Out) method, which is a method that dispenses drugs with shorter expiry dates than drugs with a later expiry date. long. With the application of the FEFO method in the Asyfa Krueng Mane Pharmacy information system, it is hoped that there will be no more accumulation of drugs and drugs with shorter expiration than drugs with longer expiration can be issued in order. As for the research results, you can see the Asyfa Pharmacy and type of Obt001 and type of Paracetamol and drug stock and date of entry and exit.